PENGEMBANGAN MEDIA POSTER BERBASIS AUDIO VISUAL UNTUK PENINGKATAN PEMAHAMAN SEKS EDUKASI PADA ANAK - Muhaimin, Muh; Sutriyani, Wulan; Wiranti, Dwiana Asih; aprilian, afinda dwi; wakit, ahmat (Universitas Islam Nahdlatul Ulama Jepara, 2023)
The occurrence of child sexual violence in the digital era has witnessed a concerning increase, exemplified by an escalation from 8,730 cases in 2020 to 2021. As of January 2022, there were already 797 recorded cases. This research aims to develop and evaluate an audio-visual-based poster media as an educational tool for children's sexual education, focusing on enhancing understanding to prevent sexual violence. Adopting a Research and Development approach, the study follows the developmental stages outlined by Plomp's model, involving needs analysis, initial design, field trials, and revisions. Data were gathered through literature reviews, interviews with sexual education experts, and field observations to formulate content suitable for children's comprehension. The development method includes designing posters with audio-visual elements such as images, diagrams, and short narratives. Expert validation was conducted to ensure the accuracy and suitability of the poster's content and design. The results of expert validation contributed positively to improvements and refinements in the design. Subsequently, the poster media underwent field trials with children to measure its effectiveness. The results of the field trials indicated an improvement in children's understanding of sexual education materials. Media validation was performed by collecting data from various sources, including feedback from teachers and parents. The results of media validation demonstrated that the audio-visual-based poster is effective in supporting children's understanding of issues related to sexuality. This study contributes to the development of an innovative and relevant sexual education media model for children in the modern era, aiming to mitigate the alarming prevalence of child sexual violence.